miR156/SPL10 Modulates Lateral Root Development, Branching and Leaf Morphology in Arabidopsis by Silencing AGAMOUS-LIKE 79 - Gao, Ruimin; Wang, Ying; Gruber, Margaret Y.; Hannoufa, Abdelali (Frontiers in Plant Science, 2018)
The developmental functions of miR156-SPL regulatory network have been extensively studied in Arabidopsis, but the downstream genes regulated by each SPL have not been well characterized. In this study, Next Generation Sequencing-based transcriptome analysis was performed on roots of wild type (WT) and miR156 overexpression (miR156OE) plants. One of the SPL genes, SPL10, which represses lateral root growth in Arabidopsis, was significantly downregulated in miR156OE plants. A transcription factor, AGAMOUS-like MADS box protein 79 (AGL79), was also significantly downregulated in the miR156OE plants, but was upregulated in the SPL10 overexpression (SPL10OE) Arabidopsis plants. In addition, SPL10 was found to bind to the core consensus SPL binding sequences in AGL79 gene. Moreover, analyses of complementation lines revealed a linear relationship between SPL10 and AGL79 in regulating Arabidopsis plant development. In addition, it was observed that plant phenotypes are AGL79 dose-dependent, with higher expression causing narrow leaf shape, less number of leaves and early flowering time, whereas relatively lower AGL79 overexpression produce plants with more rosette leaves and more lateral branches. Our findings revealed direct binding of SPL10 to AGL79 promoter, which further suggests a role for miR156/SPL10 module in plant lateral root growth by directly regulating AGL79.